Analysis of Stock Price Performance Based on Return on Investment for Indonesian Airline Companies - Abdul Muttalib; Moh. Aris Pasigai (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary objective of this study is to examine the impact of Return on Investment (ROI) on the stock prices of airline businesses that are publicly traded on the Indonesia Stock Exchange (IDX). The used approach involves the utilisation of regression analysis, which relies on secondary data derived from the financial accounts of the organisation over a specified timeframe. The research sample comprises many airline businesses that are listed on the IDX. The findings of the research indicate that the return on investment (ROI) exerts a substantial impact on the stock price of airline corporations. The findings of this study indicate a positive correlation between an increase in a company's return on investment (ROI) and a subsequent increase in its stock prices. This observation suggests that investors tend to assign greater importance to companies that are capable of generating a high return on investment (ROI). Furthermore, this study elucidates that the stock price of airline businesses can be influenced by various elements, including but not limited to economic growth, industry competitiveness, and macroeconomic considerations. Nevertheless, the primary emphasis of this study pertains to the correlation existing between return on investment (ROI) and stock prices. This study enhances comprehension regarding the significance of return on investment (ROI) in assessing the worth of a firm and its stock price within the aviation industry.